Implementation of Descriptive and Prescriptive Theory in Mastery of Arabic at SDIT Vinca Rosea Tahfizh International: Implementasi Teori Deskriptif dan Preskriptif dalam Penguasaan Bahasa Arab di SDIT Vinca Rosea Tahfizh Internasional - Ulfi Hayati (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2023)
The process of learning and learning Arabic significantly affects students in mastering vocabulary that is obtained directly or indirectly. This study was conducted to know how descriptive and prescriptive theories apply to students' mastery of Arabic and the role of teachers in improving students' mastery of Arabic at Vinca Rosea Tahfizh International Integrated Islamic Elementary School. This descriptive qualitative research targets grade 4 students with data reduction, data display, and conclusion as data analysis. The instruments used were observation, interview, and documentation. The results show that implementing descriptive language in the morning briefing activities and prescriptive language in Arabic lessons can improve students' mastery of Arabic. Namely, students can explain the meaning of Arabic vocabulary, answer simple questions, and get report cards in Arabic lessons. Both activities support each other and encourage the practice of Arabic in the school environment. The teacher's skill in providing vocabulary and uslūb and persistence in practicing the language enables students to understand and use the language in the school environment. Therefore, the equivalence of material between the morning briefing and language lessons must be considered to help students master Arabic appropriately or correctly. Keywords: Descriptive, Prescriptive, Mastery of Arabic   Abstrak Proses belajar dan pembelajaran bahasa Arab sangat mempengaruhi siswa dalam penguasaan kosakata yang diperoleh secara langsung maupun tidak langsung. Penelitian ini dilakukan dengan tujuan mengetahui bagaimana penerapan teori deskriptif dan preskriptif terhadap penguasaan bahasa Arab siswa serta peran guru dalam meningkatkan penguasaan bahasa Arab pada siswa Sekolah Dasar Islam Terpadu Vinca Rosea Tahfizh Internasional. Penelitian ini merupakan penelitian kualitatif deskriptif dengan sasaran siswa kelas 4 dengan reduksi data, display data dan conclusion sebagai analisis data. Insturmen yang digunakan berupa observasi, wawancara dan dokumentasi. Hasil yang diperoleh menunjukkan bahwa implementasi deskriptif pada kegiatan birefing (pengarahan) pagi dan preskriptif pada pelajaran bahasa Arab dapat meningkatkan penguasaan bahasa Arab siswa yaitu siswa mampu menjelaskan arti kosakata bahasa Arab, melakukan tanya jawab sederhana dan memperoleh nilai rapor pada pelajaran bahasa Arab sangat baik. Kedua kegiatan tersebut saling mendukung dan mendorong praktik berbahasa Arab di lingkungan sekolah. Keterampilan guru dalam pemberian kosakata dan uslūb serta kegigihan dalam mempraktikkan bahasa mendorong siswa memahami dan menggunakan bahasa di lingkungan sekolah. Oleh karena itu, kesepadanan materi antara briefing pagi dan pelajaran bahasa perlu diperhatikan agar membantu siswa dalam menguasai bahasa arab secara tepat ataupun benar. Kata Kunci: Deskriptif, Pengusaan bahasa Arab, Preskriptif